Collura Springs looking north, Lat 30.14 long 137.54 - Angas, George French, 1822-1886. (1859)
This drawing and several others have not been identified. This may be due to a change of name since the mid-nineteenth century. The drawing is probably of an area in the west of the North Flinders Range. The fascinating geological features would have appealed very greatly to the artist, an interest in geology being a feature of Romantic art of the late-eighteenth-into-early nineteenth-century in Europe.
Condition: good.
Title from inscription on reverse.
Also available online
Keywords: Stuart, John McDouall, -- 1815-1866 -- Journeys -- South Australia -- Pictorial works; Explorers -- South Australia -- Pictorial works; South Australia -- Discovery and exploration -- Pictorial works; Flinders Ranges Region (S.A.) -- Pictorial works